Reversion to developmental pathways underlies rapid arm regeneration in juvenile European cuttlefish, Sepia officinalis (Linnaeus 1758). Issue 3 (19th March 2019) - Callaghan, Neal I.; Capaz, Juan C.; Lamarre, Simon G.; Bourloutski, Émilie; Oliveira, Ana R.; MacCormack, Tyson J.; Driedzic, William R.; Sykes, Antonio V.
Abstract: Coleoid cephalopods, including the European cuttlefish ( Sepia officinalis ), possess the remarkable ability to fully regenerate an amputated arm with no apparent fibrosis or loss of function. In model organisms, regeneration usually occurs as the induction of proliferation in differentiated cells. In rare circumstances, regeneration can be the product of naïve progenitor cells proliferating and differentiating de novo . In any instance, the immune system is an important factor in the induction of the regenerative response. Although the wound response is well‐characterized, little is known about the physiological pathways utilized by cuttlefish to reconstruct a lost arm. In this study, the regenerating arms of juvenile cuttlefish, with or without exposure at the time of injury to sterile bacterial lipopolysaccharide extract to provoke an antipathogenic immune response, were assessed for the transcription of early tissue lineage developmental genes, as well as histological and protein turnover analyses of the resulting regenerative process. The transient upregulation of tissue‐specific developmental genes and histological characterization indicated that coleoid arm regeneration is a stepwise process with staged specification of tissues formed de novo, with immune activation potentially affecting the timing but not the result of this process. Together, the data suggest that rather than inducing proliferation of mature cells, developmental pathways are reinstated, and that a pool of naïve progenitors at the blastema site forms the basis for this regeneration. Abstract : Hypothesized process of stepwise arm regeneration in cuttlefish. Progenitor cells rapidly proliferate in the new growing arm bud, and differentiate to concentric nervous, muscular, and vascular layers in the wake of the blastema through early developmental gene programs. Finally, the potency of the blastema is exhausted and the newly‐formed tissue layers mature as the arm continues to grow with the animal. Research highlights: Juvenile cuttlefish can rapidly regenerate amputated arms in a stepwise process The regeneration process coincides with the activation of early progenitor genes Immune activation seems to delay but not inhibit regeneration